Increasing Returns Versus National Product Differentiation as an Explanation for the Pattern of U.S.–Canada Trade - Head, Keith; Ries, John (American Economic Review, 2001)
We evaluate two alternative models of international trade in differentiated products. An increasing returns model where varieties are linked to firms predicts home market effects: increases in a country's share of demand cause disproportionate increases in its share of output. In contrast, a constant returns model with national product differentiation predicts a less than proportionate increase. We examine a panel of U.S. and Canadian manufacturing industries to test the models. Although we find support for either model, depending on whether we estimate based on within or between variation, the preponderance of the evidence supports national product differentiation. (JEL F12, F15)